Solution properties of comb‐like polymers consisting of dimethylsiloxane monomer units. Issue 4 (11th February 2016) - Filippov, Alexander; Kozlov, Arkadij; Tarabukina, Elena; Obrezkova, Marina; Muzafarov, Aziz
Abstract : The increase in the rigidity of comb‐like polydimethylsiloxanes with increasing side‐chain length begins when the side chain contains more than five valent bonds. Abstract: A series of comb‐like polymers consisting of dimethylsiloxane monomer units and differing by side‐chain length have been studied in hexane solution using analytical ultracentrifugation, translational diffusion and viscometry. Analysis of the hydrodynamic parameters and their molar mass dependences based on the Fixman–Stockmayer theory or wormlike spherocylinder model shows that with side chain lengthening, the Kuhn segment length A of the polymers under study increases from the value of A for linear polydimethylsiloxane to values typical for semi‐rigid chain polymers A = 8–10 nm. © 2016 Society of Chemical Industry